Emerging Hindu Rashtra and Its Impact on Indian Muslims - Khan, M. A. Muqtedar (Religions, 2021)
This article examines the impact of the gradual Hindutvaization of Indian culture and politics on Indian Muslims. The article contrasts the status of Muslims in the still secular, pluralistic, and democratic constitution of India with the rather marginalized reality of Muslims since the rise of Hindu nationalism. The article argues that successive electoral victories by Hindu nationalist party, the Bharatiya Janata Party, has precipitated political events, generated policies, and passed new laws that are eroding the democratic nature of India and undermining its religious freedoms. The article documents recent changes that are expediting the emergence of the Hindu state in India and consequently exposes the world’s largest religious minority to an intolerant form of majoritarian governance.